2022
DOI: 10.1128/spectrum.01869-21
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of a KPC-90 Variant that Confers Resistance to Ceftazidime-Avibactam in an ST463 Carbapenem-Resistant Pseudomonas aeruginosa Strain

Abstract: For the first time, we reported a KPC variant, KPC-90, in a clinical ST463 CRPA strain with CZA resistance. CZA resistance was mediated by a 2 amino acid insertion outside the KPC omega-loop region in CRPA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 26 publications
(39 reference statements)
1
15
0
Order By: Relevance
“…The 53 studies included in this review were conducted in American, European, and Asian countries. China (14 studies) [ 14 , 15 , 17 , 19 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ], Brazil (10 studies) [ 21 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ], and Colombia (9 studies) [ 22 , 26 , 27 , 28 , 29 , 51 , 52 , 53 , 54 ] were the countries with the most reported studies, followed by Puerto Rico (4 studies) [ 55 , 56 , 57 , 58 ], Chile (2 studies) [ 59 , 60 ], Argentina (2 studies) [ 61 , 62 ], Vietnam (1 study) [ 63 ], Trinidad and Tobago (1 study) [ 64 ], Nepal (1 study) [ 65 ], India (1 study) [ 66 ], Germany (1 study) [ 18 ], Spain (1 study) [ 6 ], and the USA (1 study) […”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 53 studies included in this review were conducted in American, European, and Asian countries. China (14 studies) [ 14 , 15 , 17 , 19 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ], Brazil (10 studies) [ 21 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ], and Colombia (9 studies) [ 22 , 26 , 27 , 28 , 29 , 51 , 52 , 53 , 54 ] were the countries with the most reported studies, followed by Puerto Rico (4 studies) [ 55 , 56 , 57 , 58 ], Chile (2 studies) [ 59 , 60 ], Argentina (2 studies) [ 61 , 62 ], Vietnam (1 study) [ 63 ], Trinidad and Tobago (1 study) [ 64 ], Nepal (1 study) [ 65 ], India (1 study) [ 66 ], Germany (1 study) [ 18 ], Spain (1 study) [ 6 ], and the USA (1 study) […”
Section: Resultsmentioning
confidence: 99%
“…The current systematic review indicated that KPC-2 remains the most successful KPC variant worldwide, followed by KPC-5, which has only been reported in Puerto Rico. Recently, KPC-33 and KPC-90 variants have also been identified in Zhejiang, China, both belonging to ST463 [ 36 , 41 ]. Although all isolates have reported resistance against carbapenem antibiotics, some variants, such as KPC-90, have already shown to be resistant to more advanced combinations of antibiotics, such as ceftazidime–avibactam (CZA), a treatment that has demonstrated high efficacy against bla KPC-2 -harboring CRPA strains [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, although we did not find any KPC variants that usually result in CZA resistance in Enterobacteriaceae [23], we should still pay close attention to the CZA-resistant KPC-producing P. aeruginosa , as bla KPC-2 is a potential factor leading to CZA resistance [24], while, Tu et al have already found a KPC-90 variant that confers resistance to CZA in a clinical ST463 CRPA strain [25]. In our study, several KPC-2-producing ST463 strains showed resistance to CZA, with a MIC value of 16 µg ml −1 (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…However, with the use of CZA, CZA-resistant P. aeruginosa strains have been reported in succession, mainly due to the overexpression or amino acid substitutions/insertions/deletions of bla PDC , as well as the efflux and permeability of CZA [6]. Mutations in bla KPC have also been reported in P. aeruginosa sporadically [7].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, KPC variants showing ceftazidime-avibactam resistance have been reported in different regions of the world, commonly with high MICs, which lead to limited therapeutic options and should be fully evaluated ( 20 23 ). The two ceftazidime-avibactam disk diffusion tests showed excellent consistency with BMD for bla MBL -positive isolates (including those with bla NDM , bla IMP , bla KPC+NDM , and bla KPC+NDM+IMP ) and bla KPC-variant -positive isolates, which were all resistant to ceftazidime-avibactam by BMD.…”
Section: Discussionmentioning
confidence: 99%